2017
DOI: 10.1002/adfm.201703268
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of a Ternary Blend Solar Cell Based on Small Molecule:Conjugated Polymer:Fullerene Fabricated by Blade Coating

Abstract: Here, conjugated polymer is added as third component to tune the solution viscosity, morphology, and function of small molecule (SM) based bulk-heterojunction (BHJ) solar cells, which are fabricated using blade coating. Novel information about the effect of blade coating speed on the nanoscale morphology and function of ternary blend solar cells is provided. The crystal sizes increase with an increase of coating speed for both binary and ternary blends, while the addition of the third component tends to favor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Wu et al found that the addition of the third component can improve the morphology of BHJ layer, which was proved by a small angle neutron scattering experiment, leading to improved charge transport and device performance. [75] Zhang et al found that bladecoating can enhance the crystallinity of materials. [33] To better understand the impact of blading on films, a series of study are devoted to the observation of the film morphology The charge recombination path in the module.…”
Section: Bulk Heterojunction Solar Cellsmentioning
confidence: 99%
“…Wu et al found that the addition of the third component can improve the morphology of BHJ layer, which was proved by a small angle neutron scattering experiment, leading to improved charge transport and device performance. [75] Zhang et al found that bladecoating can enhance the crystallinity of materials. [33] To better understand the impact of blading on films, a series of study are devoted to the observation of the film morphology The charge recombination path in the module.…”
Section: Bulk Heterojunction Solar Cellsmentioning
confidence: 99%
“…It is ecofriendly, requires low-temperature processing, and has highly reliable characteristics that are needed for next-generation technologies. Solution processing includes various coating methods, such as bar coating, 16 dip coating, 17 blade coating, 18 and brush coating. [19][20][21] In particular, the brush coating method has the distinct property of adjusting the surface orientation of the molecules during the coating process using the shear stress from the solution affected by the brush hair movements.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11]. Various solution processes, including spin-coating [12], dip-coating [13], blade coating [14], and brush-coating [15,16], have been developed for advanced performance of the devices. For example, the desirable performance of optics and electronics devices can be achieved by producing high-quality polymer films or quantum dot deposition by adopting various solution coating techniques [17][18][19].…”
Section: Introductionmentioning
confidence: 99%